Relación de la enfermedad periodontal con la hiperglucemia en pacientes que acuden a la consulta odontológica de la Universidad de las Américas - Baculima López, Lorena Alexandra (2016)
The purpose of this research is to determine the relationship between periodontal diseases with hyperglycemia; participated in this study 200 patients who attended the consultation at the University of the Americas of which 54 percent were women and 46 percent men ranging in age from 18 to 70 years. In the present study it was recorded in most cases increased periodontal disease and hyperglycemia, regardless of the gender of the patient in the age group greater equal 40 years. And it was concluded that high glucose levels have a direct relationship with periodontal disease.